1962
DOI: 10.1111/j.1151-2916.1962.tb11041.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Soda Aluminosilicate Glasses: II, Internal Friction

Abstract: Vol. 45, No. 10 differently from the initial additions. The fact that the of the glass is such that its Al/Na ratio equals 1, the main Si-0 absorption band begins to shift to shorter wave-O/Al + Si ratio will equal 2 and the glass network should lengths and that the intensity of the absorption band a t be composed of A104 and SiO, tetrahedra. This network 13 to 1 4 ,~ decreases is interpreted to mean that some of the should resemble that of fused silica. aluminum ions are in different environmental surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

1981
1981
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 6 publications
2
14
0
4
Order By: Relevance
“…This fast relaxation peak has been observed in previous studies (e.g. Day and Rindone 1962b). This is the first study to observe both the a and b peaks in Na 2 O-Al 2 O 3 -SiO 2 melts in the same experiment.…”
Section: Torsion and Mechanical Spectrasupporting
confidence: 64%
See 4 more Smart Citations
“…This fast relaxation peak has been observed in previous studies (e.g. Day and Rindone 1962b). This is the first study to observe both the a and b peaks in Na 2 O-Al 2 O 3 -SiO 2 melts in the same experiment.…”
Section: Torsion and Mechanical Spectrasupporting
confidence: 64%
“…in Na 2 OSiO 2 melts. The conclusions of the studies of Day and Rindone (1962b) and Steinkamp et al (1967) have been confirmed by the modelling of Maass and Peibst (2006).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations